2012
DOI: 10.4161/jkst.20045
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 and STAT3 in tumorigenesis

Abstract: These authors contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
205
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(217 citation statements)
references
References 77 publications
11
205
1
Order By: Relevance
“…65 The binding ratio of different STAT members to the same STAT sites can affect gene expression and cell differentiation dramatically. [66][67][68] In our study, we found IL-15 stimulation dramatically activated STAT5 signaling and induced more pSTAT5 binding to the nine STAT sites on the promoter of ATM, 53BP1, MDC1 DNA damage genes. As a consequence of this binding, there are less pSTAT3, more transcriptionally repressive histones (H3K27) and less transcriptionally active histones (H3K4, P300, Acy 300) binding to the promoters.…”
Section: Discussionsupporting
confidence: 52%
“…65 The binding ratio of different STAT members to the same STAT sites can affect gene expression and cell differentiation dramatically. [66][67][68] In our study, we found IL-15 stimulation dramatically activated STAT5 signaling and induced more pSTAT5 binding to the nine STAT sites on the promoter of ATM, 53BP1, MDC1 DNA damage genes. As a consequence of this binding, there are less pSTAT3, more transcriptionally repressive histones (H3K27) and less transcriptionally active histones (H3K4, P300, Acy 300) binding to the promoters.…”
Section: Discussionsupporting
confidence: 52%
“…STAT3 activation is enhanced in STAT1-null cells, and conversely, STAT1 activation is enhanced in STAT3-null cells. 16,[60][61][62][63] Although our studies did not show a difference in STAT3 phosphorylation during re-stimulation in a Tc1 environment, STAT1 phosphorylation was significantly altered. As STAT3 and STAT1 have different functions and even oppose each other, their ratio determines the Tc17 cell phenotype.…”
Section: Discussioncontrasting
confidence: 77%
“…The JAK2/ STAT3 pathway is also downstream of other receptor tyrosine kinases, including PDGF-R (24), ILR (21,25), and EGF-R (24, 25), which are known to promote tumorigenesis in MPNSTs. STAT3 is considered an oncogene and promotes transcription of genes linked to cancer progression, driving cell migration, invasion, and survival (26). In the ST8814 cells, tyrosine phosphorylation of STAT3 was robustly induced after just 30 minutes of HGF stimulation and maintained throughout the 3-hour time course.…”
Section: Resultsmentioning
confidence: 99%